Formation and Optimization of Transport Networks in the Conditions of the Digital Integral Environment for Transportation - Boris Zhelenkov; Irina Safonova; Yakov Goldovsky; Elizaveta I. Dmitrieva (Communications - Scientific letters of the University of Zilina, 2020)
The article provides a brief description of the digital integrated transportation support environment. The methods of choosing the base route in the formation of transport networks in the conditions of the formation of a digital integrated environment are presented. It is shown that the means of solving the problem of optimization of transport networks is a developed modeling complex, which consists of a set of models with the necessary degree of detail. The paper presents a functional diagram and a brief description of the complex. The complex functions taking into account the replenishment, improvement and updating of models, allow you to combine different types of models and use the necessary of them when solving specific problems of transport network optimization. The modeling complex allows to significantly simplify the optimization of transportation networks. On the basis of the proposed mathematical apparatus, the software of an automated system has been developed, which is designed to function in a digital integrated environment, a brief theoretical description of which is given.